Anatomical Guidelines for Thigh Lipoplasty Based on Cadaveric Dissection of the Superficial Fascial System in the Thigh. Issue 2 (8th November 2022) - Si, Loubin; Li, Zhijin; Li, Hairui; Fu, Lin; Zhang, Mingzi; Qiu, Zikai; Wang, Xiaojun; Wang, Yang
Abstract : Background: Although widely accepted as an optimal procedure in thigh contouring, liposuction can result in complications, such as skin irregularity or aspiration inadequacy. A main cause might be insufficient knowledge of the superficial fascial system (SFS). The authors aimed to explore the characteristics of the SFS in the thigh and propose anatomical guidelines and new zoning for liposuction-assisted thigh contouring. Methods: A total of 20 fresh female thighs were dissected from the skin to deep fascia to observe and compare changes in the SFS from the medial to the lateral side and from the proximal to the distal end. Results: The thigh was divided into four units, namely, the medial (three subunits: upper, middle, and lower), anterior, posterior (three subunits: upper medial, upper lateral, and middle lower parts), and lateral thigh. The authors found that the form of the SFS has regional variations. Therefore, based on these varied features, four anatomical scenarios (degrees I to IV) and one functional section (hip-contour support) were devised from the eight subunits. Five different liposuction methods were formulated to manage these subunits: all-layer mass liposuction, normal aspiration, border feather-out, restricted lipoplasty, and anchor. Conclusions: The SFS of the thigh showed a regional variation pattern, based on which the authors proposed a series of new anatomy-based liposuction approaches. A well-sculpted thigh with its different sections presented in harmony can be safely obtained using these approaches.